2022
DOI: 10.3390/ijms23031448
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic, Unique and Shared Responses Elicited by IL-6 Family Cytokines in Human Vascular Endothelial Cells

Abstract: Vascular endothelial cells express glycoprotein 130 (gp130), which is utilized as a signaling receptor by cytokines in the interleukin-6 (IL-6) family. Several IL-6 family cytokines can be found in the circulatory system during physiological or pathological conditions, and may influence endothelial function and response. This study evaluated and compared the cellular and molecular responses induced by IL-6 family cytokines in human endothelial cells. A proteomic analysis showed that IL-6 family cytokines induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…IL-1β can induce its own gene expression, providing a positive feedback amplification loop for enhancing its levels at the site of inflammation. In addition, IL-1β boosts the production of IL-6 that, in turn, drives the expression of atherothrombosis mediators [ 48 ]. Notably, IL-1β also stimulates the synthesis of pro-inflammatory prostaglandins through the production of the inducible COX-2 enzyme [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β can induce its own gene expression, providing a positive feedback amplification loop for enhancing its levels at the site of inflammation. In addition, IL-1β boosts the production of IL-6 that, in turn, drives the expression of atherothrombosis mediators [ 48 ]. Notably, IL-1β also stimulates the synthesis of pro-inflammatory prostaglandins through the production of the inducible COX-2 enzyme [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Special Issue reflects the need to take into account the heterogeneity of ECs among organs and tissues and to develop EC-targeted therapeutic strategies in experimental models and for clinical applications. Illustrating this point, this issue displays studies using a variety of ECs to explore dedicated functions including human umbilical vein ECs [ 1 ], pulmonary [ 2 ], renal glomerular [ 3 ], cerebral [ 4 ] and tumor ECs [ 5 ] but also adherent versus non adherent ECs [ 6 ] and ECs isolated from adults versus young children [ 3 ]. A better understanding of microvascular ECs’ heterogeneity will provide a roadmap for developing novel therapeutics to target the endothelium.…”
Section: Include Ec Diversity To Improve Models and Design Targeted T...mentioning
confidence: 99%
“…The presence of hemoglobin during treatment with S1 protein as a mean to counterbalance hypoxic environment failed to inhibit S1 signaling in ECs. As a link between infection and inflammation, Lindkvist et al investigate how the IL-6 family cytokines, which can be found in the circulatory system during physiological or pathological conditions, may use selective receptors and signaling pathways to influence endothelial function and response [ 1 ]. Investigating the pathophysiology of hypertension in hypertensive mice after the administration of angiotensin II, Kij et al show that inhibiting thrombin prevents the development of endothelial dysfunction, increased systemic nitric oxide (NO) bioavailability, and limited endothelial inflammation but did not reduce elevated blood pressure and aortic thickening induced by angiotensin II [ 12 ].…”
Section: Endothelial Cell Signaling In Endothelial Cell Function and ...mentioning
confidence: 99%
“…During this process, the EMCN within the eGCX layer facilitates VEGFR2 internalization and downstream signaling as previously mentioned. Some systemically elevated factors may promote VEGFR2 internalization as well during HPS, such as oncostatin M (OSM) and Galectin-1/3 ( 132 , 133 ). However, since most of these results are based on experimental HPS models, whether identical mechanisms exist in humans remains to be determined.…”
Section: Potential Mechanisms Linking Egcx To the Pathogenesis Of Hpsmentioning
confidence: 99%